Stable endocytic structures navigate the complex pellicle of apicomplexan parasites - Koreny, Ludek; Mercado-Saavedra, Brandon N; Klinger, Christen M; Barylyuk, Konstantin; Butterworth, Simon; Hirst, Jennifer; Rivera-Cuevas, Yolanda; Zaccai, Nathan R; Holzer, Victoria J C; Klingl, Andreas; Dacks, Joel B; Carruthers, Vern B; et al. (Nature communications, 2023)
Apicomplexan parasites have immense impacts on humanity, but their basic cellular processes are often poorly understood. Where endocytosis occurs in these cells, how conserved this process is with other eukaryotes, and what the functions of endocytosis are across this phylum are major unanswered questions. Using the apicomplexan model Toxoplasma, we identified the molecular composition and behavior of unusual, fixed endocytic structures. Here, stable complexes of endocytic proteins differ markedly from the dynamic assembly/disassembly of these machineries in other eukaryotes. We identify that these endocytic structures correspond to the 'micropore' that has been observed throughout the Apicomplexa. Moreover, conserved molecular adaptation of this structure is seen in apicomplexans including the kelch-domain protein K13 that is central to malarial drug-resistance. We determine that a dominant function of endocytosis in Toxoplasma is plasma membrane homeostasis, rather than parasite nutrition, and that these specialized endocytic structures originated early in infrakingdom Alveolata likely in response to the complex cell pellicle that defines this medically and ecologically important ancient eukaryotic lineage.
Keywords: Endocytosis; Parasites; Animals; endocytóza; Protozoan Proteins; protozoální proteiny; paraziti; zvířata; Toxoplasma